A prospective study evaluating patterns of liver siderosis in beta-thalassemia major patients undergoing splenectomy - Basak, Souvik (Asian Journal of Medical Sciences, 2022)
Background: Hepatic iron overload resulting from multiple red cell transfusions over a long period of time is a complication of thalassemia major. Hepatocellular iron deposits with a decreasing gradient from periportal to centrilobular areas in the liver have been referred to as the HH pattern and those deposits primarily in reticuloendothelial cells and macrophages with occasional heterogeneous deposits in periportal hepatocytes are referred to as the non-HH pattern. Aims and Objectives: The purpose of this study was to evaluate patterns of liver siderosis in these patients and correlate with number of units of blood transfused. Materials and Methods: Thirty beta-thalassemia patients were selected, having splenomegaly and during splenectomy, liver biopsy was taken and sent for histopathology examination and pattern of siderosis was noted as HH (Hepatocytes), non-HH (Reticuloendothelial cells/Kupffer cells/macrophages) or HH; non-HH (Mixed). Results: Mean number of units transfused was 48.429±9.53 (SD) for patients having HH pattern of liver siderosis whereas it was 58.667±13.27 (SD) for patients having HH; non-HH pattern of liver siderosis. Independent-samples non-parametric Mann–Whitney U test was performed and P-value was found to be 0.028 which emphasized that total number of units of blood transfused vary significantly with two groups showing different patterns of siderosis. Conclusion: Hence, pattern of liver siderosis can be a good indicator for transfusional iron overload in beta-thalassemia major patients.